Toleransi Masyarakat Islam-Kristen Madura Di Desa Sumberpakem, Kecamatan Sumberjambe, Kabupaten Jember - Chriestine Lucia Mamuaya; Abdus Sair (DIMENSI - Jurnal Sosiologi, 2017)
This research describes the values and forms of tolerance between Muslim and Christian communities in Sumberpakem Village, Jember Regency. It is a village where the communities are pandhalungan. The research deploys a qualitative method by digging verbal information as much as possible related to the questions. The data analysis indicates that the tolerance values of Muslim and Christian communities in Sumberpakem Village are the universal values as reflected in multiculturalism, such as acceptance, tolerance, sympathy, empathy, and caring for cultural diversity. They are also willing to live together, mutually trust and mutually support (co-existence and pro-existence). Meanwhile, the forms of tolerance are across the religions such as joint parties, marriages, burial and occupation events.